Cohort profile: The Tromsø Study - Jacobsen, Bjarne Koster; Eggen, Anne Elise; Mathiesen, Ellisiv B.; Wilsgaard, Tom; Njølstad, Inger (International Journal of Epidemiology, 2012)
The Tromsø Study was initiated in 1974 in an attempt to help combat the high mortality of cardiovascular diseases in Norway, that was particularly pronounced among middle-aged men. In the mid-1970s, Norwegian men had a 20% risk of dying of myocardial infarction (MI) before the age of 75 years. The situation in Northern Norway was even worse.1 The primary aim of the Tromsø Study was to determine causes of the high cardiovascular mortality, and also to develop ways of preventing heart attacks and strokes. This was reflected through the first name of the study: The Tromsø Heart Study. However, during the 37 years since the first examination of the Tromsø Study took place, increasing emphasis has been put on other chronic diseases and conditions, in particular atrial fibrillation, venous thromboembolism, diabetes mellitus, osteoporosis and fractures. It has been a deliberate policy to invite a wide range of faculty research groups to join in with subprojects in the surveys, and there are currently some 100 different ongoing research projects based on the data from the consecutive six surveys. The study was initially funded by the University of Tromsø, and has been so for the entire period since 1974, but there have also been substantial contributions, directly and indirectly from, for example, the National Screening Services, the Research Council of Norway, Northern Norway Regional Health Authority, Norwegian Council on Cardiovascular Diseases and Norwegian Foundation for Health and Rehabilitation. Teams of investigators approach public research programmes for funding of the different examinations conducted. Tromsø is the largest city in Northern Norway. It is situated ∼400 km north of the Arctic Circle, and has approximately 67 000 inhabitants. The physical living conditions are dominated by dramatic changes in the light with 2 months of midnight sun and 2 months of the polar night. However, due to the Gulf Stream, the climate is relatively mild, the latitude (69°N) taken into account.